2023
DOI: 10.1186/s13048-023-01155-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of a necroptosis-related gene signature and the immune landscape in ovarian cancer

Abstract: Background Necroptosis is a novel type of programmed cell death distinct from apoptosis. However, the role of necroptosis in ovarian cancer (OC) remains unclear. The present study investigated the prognostic value of necroptosis-related genes (NRGs) and the immune landscape in OC. Methods The gene expression profiling and clinical information were downloaded from the TCGA and GTEx databases. Differentially expressed NRGs (DE-NRGs) between OC and no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…34 Several studies have suggested that MAPK10 is highly expressed in gastric and ovarian cancers and is a prognostic risk factor for tumors. [35][36][37] Our investigation verified the elevated expression of MAPK10 in SKCM tumor tissues via RT-qPCR and IHC. CCL8 (chemotactic cytokines 8) expression correlated positively with M1 macrophages, and higher CCL8 expression had significantly longer overall survival in SKCM, which may be attributed to the positive role played by M1 macrophages in anti-tumor immune activity.…”
Section: Discussionsupporting
confidence: 64%
“…34 Several studies have suggested that MAPK10 is highly expressed in gastric and ovarian cancers and is a prognostic risk factor for tumors. [35][36][37] Our investigation verified the elevated expression of MAPK10 in SKCM tumor tissues via RT-qPCR and IHC. CCL8 (chemotactic cytokines 8) expression correlated positively with M1 macrophages, and higher CCL8 expression had significantly longer overall survival in SKCM, which may be attributed to the positive role played by M1 macrophages in anti-tumor immune activity.…”
Section: Discussionsupporting
confidence: 64%
“…sig). 12 , 13 , 14 , 15 Nevertheless, the application of multigene expression signatures in clinical practice is limited due to their underutilization, utilization of inappropriate machine‐learning methods and lack of rigorous validation through additional large cohorts. To overcome these challenges, effective strategies include the development of new markers with better predictive performance or the establishment of a comprehensive rubric consisting of multiple predictive markers.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging technological tool, data mining has been widely applied in the field of medicine. It can assist researchers in extracting valuable information from massive data, such as identifying the pathogenesis of cancer ( 6 ), recognizing patients’ risk factors ( 7 ), and predicting prognosis ( 8 ). Additionally, data mining can help discover novel treatment strategies and drugs, as well as optimize existing treatment regimens.…”
mentioning
confidence: 99%